Preparation and characterization of Cr-TiO2/α-Fe2O3 nanocomposite for methylene blue degradation - Hadilala, Teguh P; Amiruddin, Erwin; Awaluddin, Amir; Setiadi, Rahmondia Nanda (Indonesian Physics Communication, 2024)
In this study, Cr-TiO2/α-Fe2O3 nanocomposite was prepared by the ball milling method, incorporating chromium, titanium dioxide (TiO2), and iron oxide (α-Fe2O3) nanoparticles extracted from Logas-Kuansing natural sand. The structural, magnetic, morphological, and optical properties of these nanocomposites were investigated using X-ray diffraction (XRD), vibrating sample magnetometer (VSM), scanning electron microscopy (SEM), and UV-Vis spectroscopy. XRD revealed that both the pure and chromium-added nanocomposites have a hexagonal structure, with a crystalline size reduction from 17.5 nm to 19.7, 19.5, and 19.4 nm for the pure and chromium-added samples with chromium concentrations of 0, 5, 10, and 15 wt.%, respectively. Magnetic properties were analyzed through hysteresis loops using VSM, revealing coercivity, saturation magnetization, and remanence magnetization in the ranges of 131 – 247 Oe, 0.80 – 0.54 emu/g, and 0.097 – 0.116 emu/g, respectively. SEM analysis confirmed that the particle shape and size are within the nanometer scale. The optical band gap, estimated using the Tauc relation, decreased from 1.93 eV for the pure nanocomposite to 1.74, 1.68, and 1.72 eV for 5, 10, and 15 wt.% chromium-added nanocomposites, respectively. This study suggests that the prepared Cr-TiO2/α-Fe2O3 nanocomposite exhibits promising physical properties as a catalyst for the degradation of methylene blue.